Effects of forage source and particle size on feed sorting, milk production and nutrient digestibility in lactating dairy cows. Issue 6 (24th September 2018) - Jiang, Fugui; Lin, Xueyan; Yan, Zhengui; Hu, Zhiyong; Wang, Yun; Wang, Zhonghua
Abstract: The objectives of this study were to determine the effects of forage source (quality) and particle size on feed sorting, milk production and nutrient digestibility in lactating dairy cows. Twelve multiparous lactating Holstein cows were used in a replicated 4 × 4 Latin square experiment with a 2 × 2 factorial arrangement of treatments. Treatments were as follows: (a) feeding long oaten hay (OL), (b) feeding short oaten hay (OS), (c) feeding long wild‐rye hay (WL) and (d) feeding short wild‐rye hay (WS). The sorting activity of cows fed wild‐rye hay diets was greater than that of cows fed oaten hay diets. Sorting activity decreased with reduced forage particle size (FPS) for wild‐rye hay diets but was not affected for oaten hay diets. Cows fed oaten hay diets had a similar dry matter intake (DMI), but higher total tract nutrient digestibility, and hence higher milk yield than cows fed wild‐rye hay diets. The increase in DMI as a result of reduced FPS was significant in cows fed wild‐rye hay diets. Feed efficiency (4% fat‐corrected milk (FCM)/DMI) decreased from 1.18 to 1.11 when FPS decreased, but was not affected by the forage source. The digestibility of DM, crude protein (CP) and organic matter (OM) in the total tract was decreased by a reduction in FPS for wild‐rye hay diets, but was not affected for oaten hay diets. In conclusion, cows fed high‐quality forage (oaten hay) had a lower sorting activity and higher production performance than those fed poor‐quality forage (wild‐rye hay). The optimal dietary FPS in lactating dairy cows should take the effect of forage source into account.